The Antiarrhythmic Mechanisms of Flecainide in Catecholaminergic Polymorphic Ventricular Tachycardia - Li, Yukun; Peng, Xiaodong; Lin, Rong; Wang, Xuesi; Liu, Xinmeng; Bai, Rong; Ma, Changsheng; Tang, Ribo; Ruan, Yanfei; Liu, Nian (Frontiers in Physiology, 2022)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a severe yet rare inherited arrhythmia disorder. The cornerstone of CPVT medical therapy is the use of β-blockers; 30% of patients with CPVT do not respond well to optimal β-blocker therapy. Studies have shown that flecainide effectively prevents life-threatening arrhythmias in CPVT, while its antiarrhythmic mechanisms are highly debated. In this article, we review the current progress of this issue.